(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Institutional repositories offer numerous advantages to academic staff as it provides access to local contents capable of enhancing their research and also offer the opportunity to make research works available to the global community. However, available evidence suggests a low level of institutional repository use among academic staff in Nigerian universities. This study examines the role of multidimensional awareness on the use of institutional repositories. The study adopts a survey research method. The study population is made up of academic staff from Universities in Oyo and Osun state. A multistage sampling procedure is adopted to select 235 lecturers. The research instrument is a structured questionnaire adapted from the Endsley’s Situational Awareness Theory (SAT). Data collected was analysed using both descriptive and inferential statistics. The results showed that while there is a high level of perception among the respondents, majority of the respondents’ demonstrated low level comprehension and projection two elements critical to the understanding of the true essence of institutional repositories. In addition, the test of hypothesis revealed that awareness has a significant influence on the use of institutional repositories among the respondents. The study concluded that, without raising full awareness about the mission and functions of institutional repositories, Nigerian tertiary institution and their staff will continue to miss out on the benefits of using institutional repositories. It was therefore recommended that institutional repository awareness programs should be practical oriented.